Subordinate clauses of time with conjunctions referring to limito r boundary - Pajėdienė, Jūratė (Lietuvių kalba, 2009)
Subordinate clauses of time with the conjunctions referring to a limit or boundary kol, iki, ligi can express not only relations of a sequence of events/situations or simultaneity, but also highlight duration and indicate efforts put into the performance of the action. Verbs in the main and subordinate clauses can make certain combinations of tense forms. The selection of a subordinate clause structure depends on the modality of the predicate in the main clause. In cases of epistemic modality, main and subordinate clauses are based on verb forms expressed by the same tense. Cases, when tense forms differ, in such sentences are concerned with the de dicto semantic relation. When the predicate of the main clause expresses deontic modality, for the subordinate clause of time the following type of structure is selected: a conjunction referring to a temporal limit or boundary + negation + verb in the past simple tense. Clauses of time are characterised by specific structural peculiarities and a higher degree of grammaticality, semantically they are related to a need to describe a situation of imminent change or a situation set against the background of the other situation.